PENGARUH STRATEGI PROBLEM-BASED LEARNING DAN MINAT BELAJAR TERHADAP HASIL BELAJAR IPA SISWA DI SD NEGERI KECAMATAN IDANOGAWO KABUPATEN NIAS TAHUN AJARAN 2022/2023 - Lianus Zebua; Efendi Napitupulu; Maximus Gorky Sembiring; Syahril . (Jurnal Teknologi Pendidikan (JTP), 2024)
Abstract: The aim of this research is to analyze the influence of Problem-Based Learning (PBL) strategies and interest in learning on science learning outcomes. Data were analyzed using two-way ANOVA, 2×2 factorial with questionnaire instruments, a valid and reliable test. The results of the study: (1) There is an influence of the PBL strategy on science learning outcomes. The science learning outcomes of students who were taught using the PBL strategy were higher, compared to students who were taught with the expository learning strategy; (2) There is an influence of learning interest on science learning outcomes. (3) There is an interaction between PBL strategies and learning interest on science learning outcomes. Keywords: Learning Outcomes, PBL Strategies, Expository Learning Strategies. Abstrak: Tujuan penelitian ini adalah untuk menganalisis pengaruh strategi Problem-Based  Learning (PBL) dan minat belajar terhadap hasil belajar IPA. Data dianalisis dengan  ANAVA dua jalur, faktorial 2×2 dengan instrumen angket, tes yang valid dan reliabel. Hasil penelitian: (1) Terdapat pengaruh strategi PBL terhadap hasil belajar IPA.  Hasil belajar IPA siswa yang diajarkan dengan strategi PBL lebih tinggi, dibandingkan siswa yang diajarkan dengan strategi pembelajaran ekspositori. (2) Terdapat pengaruh minat belajar  terhadap hasil belajar IPA. (3) Terdapat interaksi antara strategi PBL dan minat belajar terhadap hasil belajar IPA.  Kata Kunci: Hasil Belajar, Strategi PBL, Strategi Pembelajaran Ekspositori.